Exercise-induced dehydration with and without environmental heat stress results in increased oxidative stress - Hillman, A. R.; Vince, R. V.; Taylor, L.; McNaughton, L.; Mitchell, N.; Siegler, J. (Applied Physiology, Nutrition, and Metabolism, 2011)
While in vitro work has revealed that dehydration and hyperthermia can elicit increased cellular and oxidative stress, in vivo research linking dehydration, hyperthermia, and oxidative stress is limited. The purpose of this study was to investigate the effects of exercise-induced dehydration with and without hyperthermia on oxidative stress. Seven healthy male, trained cyclists (power output (W) at lactate threshold (LT): 199 ± 19 W) completed 90 min of cycling exercise at 95% LT followed by a 5-km time trial (TT) in 4 trials: (i) euhydration in a warm environment (EU-W, control), (ii) dehydration in a warm environment (DE-W), (iii) euhydration in a thermoneutral environment (EU-T), and (iv) dehydration in a thermoneutral environment (DE-T) (W: 33.9 ± 0.9 °C; T: 23.0 ± 1.0 °C). Oxidized glutathione (GSSG) increased significantly postexercise in dehydration trials only (DE-W: p < 0.01, DE-T: p = 0.03), and while not significant, total glutathione (TGSH) and thiobarbituric acid reactive substances (TBARS) tended to increase postexercise in dehydration trials (p = 0.08 for both). Monocyte heat shock protein 72 (HSP72) concentration was increased (p = 0.01) while lymphocyte HSP32 concentration was decreased for all trials (p = 0.02). Exercise-induced dehydration led to an increase in GSSG concentration while maintenance of euhydration attenuated these increases regardless of environmental condition. Additionally, we found evidence of increased cellular stress (measured via HSP) during all trials independent of hydration status and environment. Finally, both 90-min and 5-km TT performances were reduced during only the DE-W trial, likely a result of combined cellular stress, hyperthermia, and dehydration. These findings highlight the importance of fluid consumption during exercise to attenuate thermal and oxidative stress during prolonged exercise in the heat.